Design of a basigin‐mimicking inhibitor targeting the malaria invasion protein RH5. Issue 1 (2nd August 2019) - Warszawski, Shira; Dekel, Elya; Campeotto, Ivan; Marshall, Jennifer M.; Wright, Katherine E.; Lyth, Oliver; Knop, Orli; Regev‐Rudzki, Neta; Higgins, Matthew K.; Draper, Simon J.; Baum, Jake; Fleishman, Sarel J.
Abstract: Many human pathogens use host cell‐surface receptors to attach and invade cells. Often, the host‐pathogen interaction affinity is low, presenting opportunities to block invasion using a soluble, high‐affinity mimic of the host protein. The Plasmodium falciparum reticulocyte‐binding protein homolog 5 (RH5) provides an exciting candidate for mimicry: it is highly conserved and its moderate affinity binding to the human receptor basigin ( K D ≥1 μM) is an essential step in erythrocyte invasion by this malaria parasite. We used deep mutational scanning of a soluble fragment of human basigin to systematically characterize point mutations that enhance basigin affinity for RH5 and then used Rosetta to design a variant within the sequence space of affinity‐enhancing mutations. The resulting seven‐mutation design exhibited 1900‐fold higher affinity ( K D approximately 1 nM) for RH5 with a very slow binding off rate (0.23 h −1 ) and reduced the effective Plasmodium growth‐inhibitory concentration by at least 10‐fold compared to human basigin. The design provides a favorable starting point for engineering on‐rate improvements that are likely to be essential to reach therapeutically effective growth inhibition.